Drug prescription pattern in exotic pet and wildlife animal practice: a retrospective study in a Spanish veterinary teaching hospital from 2018 to 2022 - Romero, Beatriz; Susperregui, Julen; Sahagún, Ana M.; Fernández, Nélida; López, Cristina; de la Puente, Raúl; Altónaga, José R.; Díez, Raquel (Frontiers in Veterinary Science, 2024)
Exotic companion animals have had an important role in our society since ancient times. To preserve animal health is necessary to do a responsible use of veterinary medicines. This study aims to describe the prescription patterns of drugs in exotic pets and wildlife animals attending at the Veterinary Teaching Hospital of the University of León (HVULE). A retrospective study was carried out between 2018 and 2022. Birds were the largest group of exotic animals attending the HVULE. Visits were related to emergency reasons, and for musculoskeletal disorders. One third of the animals was eventually euthanised. Regarding pharmacological treatments, the most frequently active ingredients used were pentobarbital, isoflurane, meloxicam, and within antibiotics, marbofloxacin (category B in the classification of European Medicines Agency).